Republic of Slovenia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper analyzes the challenges that the Republic of Slovenia will face in the coming years. It examines the efficiency of the Slovene banking sector in the European Union context. The paper analyzes indicators of bank efficiency by comparing performance indicators for banks in Slovenia, the European Monetary Union, and new member states. It presents results from cross-country econometric estimates of banking sector cost efficiency. The paper also discusses results from estimates of cross-country banking sector contestability, and the determinants of efficiency and contestability.